Peran Orang Tua dalam Menanamkan Nilai-Nilai Agama Islam pada Anak - Leni, Sismi; Adisel, Adisel (JOEAI (Journal of Education and Instruction), 2021)
The purpose of this study was to describe the role of parents in instilling Islamic religious values ​​in children and to analyze what factors influence the role of parents in instilling Islamic religious values ​​in children in Dusun Pulau Village, Air Rami District, Mukomuko Regency, Bengkulu Province. . This type of research is qualitative research. Collecting data using observation, interviews and documentation. The results of the study, the role of parents in instilling Islamic religious values ​​in children in the family, namely being educators/teachers at home, parents as facilitators, parents as advisers and supervisors for children and parents giving influence to children. Factors that influence the role of parents in instilling Islamic religious values ​​in children are first the family environment, household atmosphere caused by working parents so that parents find it difficult to distribute time between work and children; the two school environments in this study are informal school environments, namely very adequate TPA such as; learning facilities and competent teachers, the third community environment that is influenced by friends to hang out with. In conclusion, the role of parents in instilling Islamic religious values ​​in children based on research results has played a good role, several factors influence the role of parents in instilling Islamic religious values ​​in children in Dusun Pulau Village, Air Rami District, Mukomuko Regency, Bengkulu Province, namely family environmental factors, school environmental factors and community environmental factors. Keywords: Instilling, Islamic religious values, the role of parents